PENGARUH EKSTRAK Sargassum cristaefolium PADA MULTIPLIKASI Dendrobium antennatum Rchb.f SECARA IN VITRO - Ansyarif, Faisal; Ghazali, Mursal; Muspiah, Aida; Kurnianingsih, Rina (Bioscientist : Jurnal Ilmiah Biologi, 2020)
The purpose of this study was to determine the potential and concentration of Sargassum cristaefolium extract as a natural cytokinin in tissue culture media of Dendrobium antennatum Rchb.f. This study is experimental with a completely randomized design, using several extract concentrations compared with the positive control (BAP 1.5 ppm) and negative control (MS0 media). Extract concentrations used 5 ppm, 10 ppm, 15 ppm, 20 ppm, and 25 ppm. Based on analysis of variance (ANOVA), the effect of Sargassum cristaefolium extract on the growth media significant on all parameters. Sargassum cristaefolium extracts caused different responses at certain levels of concentration. Extract concentration of 10 ppm was able to initiate the highest number of shoots and leaves compared to other extract concentrations, where as the concentration 20 ppm was able to accelerate and increase root growth.